Sustainability Strategy Analysis for Clay Industry in Godean Distric - Fajrin, Annisa Rahma; Budiani, Sri Rahayu (Jurnal Ilmu Ekonomi Terapan, 2020)
The clay industry in Godean Distric existed due to proximity of its raw material. The clay industry has been established since 1930 and began to stop producing. The strategy is needed to maintain the sustainability of this production activity. The aim of this research is to formulate the sustainable strategy using the SWOT analysis. The SWOT analysis is formulated with internal and external factors that influence the sustainability of this industry. The data is analized with descriptive qualitative technique using IFAS Table, EFAS Table, IE Matrix, and SWOT Matrix. The results show that the internal factors are management, the product reputation, inovation, capital, labour, raw material, and business sucessors. The external factors are market, the existance of Asosiasi Pengrajin Genteng, government policies, suppliers and distributors, and competitors. The right strategy to maintain the sustainability of the clay industry is to avoid losing profit and extend the market. One of right way to do is making the own brand.